ทัศนคติของประชาชนในอำเภอเมืองเชียงใหม่ต่อ การประกันชีวิตแบบบำนาญ - สิทธิพงศ์ วงศ์ษาพาน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aimed to examine the attitude of people in Amphoe Mueang Chiang Mai towards life insurance for retirement policy. Populations in this study were specified to 373 samples residing in Amphoe Mueang Chiang Mai in the age of 30-55 years old in accordance with the convenient sampling method. Questionnaires were used as the tool to collect data. The data obtained were, then, assessed by statistics namely frequency, percentage, and mean. The findings presented that most respondents were married female in the age of 30-35 years old with bachelor’s degree. They worked as private company employee and earned monthly income at the over amount of 70,0001 Baht. Most of them had already carried life insurance. According to the study on three attitude components: cognitive, affective, and behavioral components of the people in Mueang Chaing Mai district, the results showed that those who were in a group of people with life insurance for retirement policy were aware that the life insurance for retirement policy was the policy with over 10 years of ceasing age, with the return of profit when the insurer aged at 55 – 85 years old or over, and with the tax reduction privilege which was limited to the policy attached by the parentheses stating that “retirement policy with tax reduction”, respectively. For those who were in a group of people without life insurance for retirement policy, they were aware that the life insurance for retirement policy was the policy that could be used to deduct the assembling income tax at the maximum of 15 percent for the maximum amount of income at 200,000 Baht. They were also aware that it was the policy with over 10 years in period and with the return of profit when the insurer aged at 55-85 years old or over, respectively. The top three elements in affective component that the respondents with life insurance for retirement policy ranked were to be the policy fostering an insurer to accumulate pension to secure their retirement age, to serve as security for the insurer and his/her family in the future, and the fame of insurance company affecting decision making towards the life insurance for retirement policy, respectively. The top three elements in affective component that the respondents without life insurance for retirement policy ranked were to serve as security for the insurer and his/her family in the future, the fame of insurance company affecting decision making to have the life insurance for retirement policy, and the knowledge and advices as offered by an insurance agent affecting decision making towards the life insurance for retirement policy, respectively. The top three elements in behavioral component that the respondents with life insurance for retirement policy ranked were respectively compiled from different aspects as follows: the top element in aspect of reason of having life insurance for retirement policy was to be another saving type; the top element in aspect of source of information where they learned about the product prior to purchase was the insurance agent; and the top element in an important aspect arousing their interest to have the life insurance for retirement policy was the income as gained during retirement period. The top three elements in behavioral component that the respondents without life insurance for retirement policy ranked were respectively compiled from different aspects as follows: the top element in aspect of reason of not purchasing life insurance for retirement policy was to have long term obligations; the top element in aspect of source of information influencing their decision making to have life insurance for retirement policy in the future was the insurance agent; and the top element in an aspect arousing them to have the life insurance for retirement policy in the future was the income as gained during retirement period.